2022
DOI: 10.3390/app122312351
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beech Bark Extract in the Reduction of Discomfort from Acute Pericoronitis

Abstract: Pericoronitis is characterized by inflammation of the tissues surrounding an erupting tooth and occurs most commonly in lower wisdom teeth. The extent of inflammatory phenomena can significantly affect the patient’s quality of life because of the pain, bleeding, and discomfort caused by it. The treatment of pericoronitis is carried out locally by irrigation and debridement in the early stages, but also generally by antibiotic therapy, when purulent secretion is present under the operculum and in the periodonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The parameters evaluated were pain, trismus and bleeding index. The results showed that BBE-based irrigation more effectively reduced pain, trismus and bleeding compared to the alternative solutions [18].…”
mentioning
confidence: 97%
“…The parameters evaluated were pain, trismus and bleeding index. The results showed that BBE-based irrigation more effectively reduced pain, trismus and bleeding compared to the alternative solutions [18].…”
mentioning
confidence: 97%